Platelet-Rich Plasma Versus Hyaluronic Acid for Knee Chondral Injuries in Young Patients - Danieli, Marcus Vinicius; Guerreiro, João Paulo Fernandes; Vimercati, Telvio Ataide; Mendes, Pedro Henrique Favaro; Miyazaki, Paulo Raphael Tsutomu Katayama; Cataneo, Daniele Cristina [UNESP] (Thieme, 2021)
Objective The present study aimed to compare the clinical and functional outcomes of hyaluronic acid (HA) or platelet-rich plasma (PRP) applications to treat young patients with knee chondral lesions with no arthrosis. Methods Prospective clinical and functional evaluation of 30 young adult patients with knee chondral lesions submitted to conservative treatment with HA or PRP for a minimum follow-up time of 12months. TheWestern Ontario and McMaster Universities Arthritis Index (WOMAC) and visual analog scale (VAS) were used for the evaluation. Results According to the WOMAC score, the PRP group showed significant improvement in all evaluated points, whereas the HA group presented no score improvement. In the VAS, the PRP group showed improvement in all evaluated points, and the HA group presented improvement at 6 and 12 months. Compared to the HA group, the PRP group presented better WOMAC scores at all evaluated points and better VAS scores up to 6 months after treatment. Conclusion Platelet-rich plasma application resulted in better clinical and functional outcomes at both the WOMAC and VAS scores when applied to knees from young patients with chondral lesions, but no arthrosis. These outcomes were sustained for up to 12months. Level of evidence Randomized clinical trial (Type 2B).
Comparação entre viscossuplementação e plasma rico em plaquetas em lesões condrais de joelhos de pacientes jovens
Keywords: cartilage, articular; Hyaluronic acid; knee; platelet-rich plasma; viscosupplementation